Evaluasi Stabilitas dan Penanganan Lereng Produk Aktivitas Vulkanik Kuarter Pada Pembangunan Jalan Baru Shortcut 4 BTS. Kota Singaraja – Mangwitani, Bali - Daru Jaka Sasangka; Rakhman Taufik; Afriza Noor (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2022)
Potential problems of rock-slope landslide were found in the construction of the new shortcut 4 road on the BTS national road section from Singaraja City to Mangwitani, Bali, Indonesia. The source of landslide potential is from andesite with intense stiffness found during excavation work of the road body. The potential for rock-slope landslides can threaten the bridge abutment building above. The andesite-slope product location of shallow intrusion is exactly on the shores of Lake Bratan. This study aims to determine the level of elevation of the slope based on each type of failure as well as empirical treatment recommendations. The research method was done by applying a local geological mapping to determine rock types, field measurements by scanning rock outcrop locations, and a calculation of rock-mass-quality values ​​using the Rock Mass Rating (RMR) method. Whereas the Rock Quality Assessment was carried out using the Rock Mass Rating (RMR) method, the slope evaluation was carried out using the Slope Mass Rating (SMR). The study used types of potential landslides and values, namely, planar landslides with an SMR value of 30.18 (Unstable) and a landslide probability of 0.6, wedge landslides with an SMR value of 57.6 (Partially Stable) and a landslide probability of 0.4, and the potential for tipping landslides with an SMR value of 47.6 (Partially Stable) and a landslide probability of 0.4. SMR values ​​indicate that rock slopes require further handling/treatment to get a stable slope. In addition, the slope angle of 650 is sufficient.